The state of civil necessity in the face Of the covid-19 pandemic: a critical approach - Ninamancco Córdova, Fort (2020)
This work seeks to outline a critical analysis on the applicability of the state of civil necessity, provided for in paragraph 3 of article 1971 of the Civil Code, in the context of the socio-economic crisis generated by the Covid-19 pandemic. Thus, taking as a reference to European doctrinal approaches, the author critically approaches the national doctrine and the regulations of our Civil Code, establishing some guidelines that must be taken into account when evaluating such applicability, which has been neglected in the civilistas debates that have occurred regarding the pandemic.